Incidence, management, and outcomes of pregnancies complicated by major placenta praevia at Tygerberg Hospital: A two-year review - Indongo, Justine Nalimanguluke (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed) -- Stellenbosch University, 2022.